Active share and fund performance : Evidence from Finland - Laaksonen, Vinski (My University, 2023)
This thesis examines the level of active portfolio management within Finnish funds that mainly invest in Finnish equities. As passive funds have generally attracted more flows than their active counterparts, the discussion of the relevance of active investing is topical. In this thesis, the level of active management is observed using a measure called Active share. Active share measures the actual level of active portfolio management by comparing the overlap between portfolio holdings and portfolio benchmark index holdings. In contrast to traditional tracking error, Active share indicates the level of active management more precisely. As there is no unanimous consensus on whether high Active share funds generate excess returns compared to the benchmark, there is room for further examination, especially in Finnish markets. In this thesis, the impacts of Active share are examined by studying pure data characteristics as well as utilizing a panel regression model. The relation between Active share and fund performance is tested using pure gross returns, risk-adjusted returns and benchmark-adjusted returns. The sample consists of 17 active Finnish mutual funds that mainly invest in Finnish equities during an examination period of 6/2016 – 6/2021. Additionally, the overall level of active management in Finland is studied as well as the presence of closet indexing. The thesis provides evidence that Finnish funds mainly investing in Finnish equities are considerably passive and closet indexing is overrepresented within the sample. The share of truly active funds, measured by Active share, is minimal in Finland. As the funds are considerably passive, the sample does not give support for testing for the relation between high Active share funds and fund performance. Even though the used data does not provide significant evidence of Active share’s ability to predict future returns, it provides a clear benefit of Active share being used in evaluating a suitable level of fees a fund charges for active management. The findings of this thesis suggest a fund investor to choose from the funds with the lowest fees as active management in Finland does not seem to generate reliably greater returns.

Tämä tutkielma tarkastelee aktiivista salkunhoitoa suomalaisten pääosin suomalaisiin osakkeisiin sijoittavien sijoitusrahastojen keskuudessa. Sijoitusvarallisuuden siirtyessä yhä passiivisempiin rahastovaihtoehtoihin, on aktiivisten sijoitusrahastojen olemassaolon relevanttius ajankohtaista. Tässä tutkielmassa aktiivista salkunhoitoa tutkitaan Active share -mittarilla. Active share mittaa sijoitusportfolion todellisen aktiivisuuden suhteuttamalla sijoitusten päällekkäisyyden portfolion sekä vertailuindeksin välillä. Perinteiseen Trackin erroriin verrattuna Active share indikoi portfolion aktiivisuutta täsmällisemmin. Koska korkean Active sharen yhteyttä parempaan rahaston performanssiin ei ole yksimielisesti voitu todeta, on aihepiirissä tilaa uusille tutkimuksille, etenkin Suomen markkinoilla. Tässä tutkielmassa, Active sharen vaikutuksia tutkitaan tarkastelemalla aineiston ominaispiirteitä sekä regressiomallia hyödyntäen. Active sharen ja rahaston performanssin välistä yhteyttä testataan käyttäen puhdasta bruttotuottoa, riskikorjattua tuottoa sekä indeksikorjattua tuottoa. Aineisto koostuu 17 suomalaisesta rahastosta, jotka sijoittavat pääosin suomalaisiin osakkeisiin tarkastelujaksolla 6/2016 – 6/2021. Lisäksi tutkielmassa tarkastellaan yleistä salkunhoidon aktiivisuuden tasoa sekä kaappi-indeksoinnin esiintymistä tarkastelujoukossa. Tutkielma osoittaa, että suomalaiset pääosin suomalaisiin osakkeisiin sijoittavat sijoitusrahastot ovat huomattavan passiivisia ja kaappi-indeksointia esiintyy runsaasti. Varsinaisten aktiivisten sijoitusrahastojen osuus on Suomessa minimaalinen Active sharella mitattuna. Aineiston rahastojen ollessa huomattavan passiivisia, aineisto ei tue korkean Active sharen ja rahaston tuoton välisen yhteyden testaamista pidemmälle. Vaikka tutkielman aineisto ei tarjoakaan merkittävää näyttöä Active sharen kyvystä ennustaa rahaston tulevia tuottoja, on Active sharen käytöstä selvää hyötyä arvioitaessa rahaston kulurakenteen sopivuutta. Tutkielman löydökset ohjaavat rahastosijoittajaa valitsemaan sijoituskohteen matalimman kulurakenteen rahastojen joukosta, sillä aktiivinen salkunhoito ei näytä Suomessa takaavan todistetusti parempia tuottoja.
Keywords: fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance